2004
DOI: 10.1080/02664760410001681738
|View full text |Cite
|
Sign up to set email alerts
|

EWMA Chart and Measurement Error

Abstract: A Measurement error is a usually met distortion factor in real-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 18 publications
6
71
0
Order By: Relevance
“…The results reveal that as the ratio σ 2 m /σ 2 increases, the CUSUM charts need more data (time) to detect a shift than in the no error case. Similar results were reported by Linna and Woodall [11] as well as Maravelakis et al [15].…”
Section: Effect Of Measurement Errorsupporting
confidence: 88%
See 1 more Smart Citation
“…The results reveal that as the ratio σ 2 m /σ 2 increases, the CUSUM charts need more data (time) to detect a shift than in the no error case. Similar results were reported by Linna and Woodall [11] as well as Maravelakis et al [15].…”
Section: Effect Of Measurement Errorsupporting
confidence: 88%
“…They considered the EWMA-X-S chart which is a combination of the EWMA charts for the mean and the standard deviation. Maravelakis et al [15] examined the case of the EWMA control chart for the mean assuming the model introduced in Linna and Woodall [11]. Shore [20] dealt with the problem of designing Shewhart control charts under the presence of measurement error.…”
Section: Introductionmentioning
confidence: 98%
“…But, in many industrial scenarios, there often exist significant measurement errors that affect the performance of control charts. Since Bennet (1954) investigated the effect of measurement errors on the ShewhartX chart, there are many studies about the actual performance of various control charts in the presence of measurement error, for further details see for instance: Kanazuka (1986), , Linna, Woodall, and Busby (2001), Maravelakis (2004), Costa and Castagliola (2011), Maravelakis (2012). Recently, Hu et al (2015) investigated the performance of the syntheticX chart when measurement errors exist using a linear covariate error model and they showed that the performance of the syntheticX chart is significantly affected in the presence of measurement error.…”
Section: Introductionmentioning
confidence: 99%
“…Further researches are in progress for evalauting the efficiency of other types of multivariate control charts (Multivariate Cumulative Sum [11] and Multivariate Exponentially Weighted Moving Average [12]) for monitoring small and moderate shifts in the mean vector. …”
Section: Discussionmentioning
confidence: 99%